Proceedings of the 52nd Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2014
DOI: 10.3115/v1/p14-1008
|View full text |Cite
|
Sign up to set email alerts
|

Logical Inference on Dependency-based Compositional Semantics

Abstract: Dependency-based Compositional Semantics (DCS) is a framework of natural language semantics with easy-to-process structures as well as strict semantics. In this paper, we equip the DCS framework with logical inference, by defining abstract denotations as an abstraction of the computing process of denotations in original DCS. An inference engine is built to achieve inference on abstract denotations. Furthermore, we propose a way to generate on-the-fly knowledge in logical inference, by combining our framework w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The experimental results on the FraCaS test suite have shown that a reasonable number of lexical entries and non-first-order axioms enable various logical inferences in an efficient way and outperform the state-of-the-art first-order system. Future work will focus on incorporating a robust model of lexical knowledge (Lewis and Steedman, 2013;Tian et al, 2014) to our framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results on the FraCaS test suite have shown that a reasonable number of lexical entries and non-first-order axioms enable various logical inferences in an efficient way and outperform the state-of-the-art first-order system. Future work will focus on incorporating a robust model of lexical knowledge (Lewis and Steedman, 2013;Tian et al, 2014) to our framework.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware of two other systems tested on FraCaS that are capable of multiple-premise inferences: the CCG-based first-order system of Lewis and Steedman (2013) and the dependency-based compositional semantics of Tian et al (2014). These systems were only evaluated on the Quantifier section of FraCaS.…”
Section: Methodsmentioning
confidence: 99%
“…Labels on the two ends of an edge, initially indicating fields of tables in a database, are considered as semantic roles of the corresponding words. Abstract denotation is proposed to capture the meaning of this abstract version of DCS tree, and a textual inference system based on abstract denotation is built (Tian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 Alignment with logical clues Tian et al (2014) proposed a way to generate onthe-fly knowledge to fill knowledge gaps: if H is not proven, compare DCS trees of T and H to generate path alignments (e.g. blamed for death ∼ cause loss of life, as underscored in Figure 1); evaluate the path alignments by a similarity score function; and path alignments with a score greater than a threshold (0.4) are accepted and converted to inference rules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation